Derridean deconstruction as a viable framework for a student-oriented philosophy of teaching - Paras, Percival S. (Animo Repository, 2023)
This study’s main claim is that Derridean deconstruction, as a critical strategy, is a viable Other-oriented philosophy of teaching that will bridge the gaps in, as well as address the limitations and incoherence of, the traditional teacher-centered paradigm of education. Similarly, this study is also geared towards making a critique of the student-centered paradigm of teaching and learning as it posits possible malpractice that leads to what I call academic othering in education. This claim is proven by citing the different criticisms of both teacher-centered and student-centered paradigms, but focusing on academic othering rooted in violence. Derridean deconstruction is presented as the solution to the problems of these two paradigms. To arrive at this, the discussion proceeds through the following steps: first, by defending deconstruction against charges of nihilism and relativism; second, by critiquing the malpractices of critical thinking such as critical dogmatism and transcendental critique, and presenting deconstruction as an alternative; and third and last, by pointing to Derrida’s concepts of hospitality and justice as essential to a teaching approach that espouses “friendship informed by différance”. In the first step, the study accounts the different charges against the nature of Derrida’s philosophy. Charges of nihilism against deconstruction may posit this approach as inappropriate for a teaching philosophy, but through Derrida’s defense of his philosophy, deconstruction is proven affirmative. In relation to that, deconstruction is also defensible against the charge of relativism and skepticism, making it viable as a teaching philosophy. In the second step, deconstruction provided a better alternative to the practice of critical thinking as it is defensible from the problems of critical dogmatism and transcendental critique. These two malpractice in criticality make deconstruction a more critical approach. Relative to this discourse are examples of critical theory and other methods intended to show critical thinking in the 21st century. In this step, Derrida’s deconstruction is proven to be a more critical approach to teaching and learning. In the last step of this study, Derridean deconstruction answers the issues of academic othering rooted in what Derrida calls violence. In this discussion, Derrida’s view of alterity is compared with Levinas’s responsibility towards the Other. In the end, the former is presented as a more suitable approach to teaching and learning as it caters to the authenticity of the Other and establishes balance of power between the I and the Other through negotiation and friendship. Overall, Derridean deconstruction is defensible as a viable framework for an Other-oriented philosophy of teaching.